Child Mental Health Services in the Emergency Department: Disparities in Access. Issue 7 (July 2015) - Lynch, Sean; Bautista, Maria; Freer, Cecilia; Kalynych, Colleen; Hendry, Phyllis
Abstract : Objective: Recent research suggests that increasing numbers of caregivers are bringing their children to the emergency department (ED) for mental health services and that a large proportion of these children have Medicaid as their insurance. The objective of this study was to examine the characteristics of children with Medicaid who present with psychiatric conditions in Florida hospital EDs. Methods: A retrospective research design was used, and the insurance claims of children who went to the ED for mental health care were analyzed. A logistic regression model was constructed to determine whether age, race, ethnicity, sex, and residence in an area with mental health professional shortage increased the odds of a psychiatric ED visit for children with Medicaid. Results: All 5 predictor variables were significantly associated with the likelihood of an ED visit for mental health reasons by children with Medicaid. Conclusions: The ED is an entry point into the child mental health system of care for children with Medicaid.